An Investigation on Consumer Behavior Concerning “Trendy Drink” in Islamic View - Syafira, Shofwah; Wijayanti, Farah Nur Syafi`ah; Wildatika, Nerning Galidha (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
This study was aimed to determine drivers of consumer trust, satisfaction and recommendation to others regarding “Trendy Drink” Mixue Ice Cream & Tea. Based on literature review, most of consumer behavior studies were investigated by a single method. Furthermore, research on consumer perspectives concerning food safety in Islamic were still limited. Hence, we extended this study using mixed method. Sampling used is purposive with characteristics Moslem, 17 years old or over and has purchased Mixue Ice Cream and tea in the outlet. Firslty, open-ended interviews were carried out to gather data amplified by second phase of data collection was online survey and the data of 234 participants were analyzed utilizing SEM-PLS. Study revealed that consumers perceived food as safe attributed to its appearance, taste, smell, certification and quality. Additionally, study uncobered that food safety and information credibility were prominent drivers of consumer behavior. This paper explored an underexposed concern on product safety in Islamic view. It contributes to the marketing field empirically, theoretically and practically by extending the implementation of food safety, source of credibility theory, and Maslow`s hierarchy of need theory in the Islamic marketing and food & beverages context. Additionally, applying a mixed-method for data analysis broadened the research results` generalisability.